Cultivo da melancia nos sistemas de plantio direto e convencional - Silva, Márcio Gledson Oliveira da (2010)
This study aimed to evaluate strategies for weed management on the production of watermelon, in no-tillage and conventional systems, after melon cultivation. The experiment was conducted in split plots, distributed in randomized block design, with four replications. In the plots were evaluated the tillage systems (no tillage and conventional tillage) and in the sub-plots were evaluated nine systems of weed management (covered with polyethylene film, with weeding at 14 days after transplanting (DAT); at 14 and 28 DAT, at 14 and 42 DAT, at 14, 28 and 42 DAT, at 28 DAT, at 28 and 42 DAT, at 42 DAT and without weeding control). It was evaluated density and dry weight of weeds at 14, 28 and 42 DAT and at harvest time (80 DAT). For the watermelon were evaluated number of marketable fruit per plant, total fruit number per plant, average weight of marketable fruit per plant, average mass of fruits (total) per plant, marketable and total yield of fruit, besides the qualitative characteristics (longitudinal and transverse length, pulp thickness and firmness, pH and soluble solids). The no-tillage system reduced the density and dry mass of weeds and proportionated fruit yield bigger than the conventional tillage system. In conventional tillage was necessary to carry out weeding at 14 and 28 DAT, while in no-tillage system, despite the lower weed infestation, there was need to do only one weeding between 28 and 42 DAT. In the treatments without weeds control there was reduction of 100 and 35.7% in marketable yield, respectively, for conventional and no-tillage systems. The no-tillage system and cover with polyethylene film in the conventional tillage allow the accomplishment of a second crop in the area in succession to the melon, reducing weed interference and providing satisfactory results in the characteristics of watermelon production.